Enhancing Quality Assurance through Harmonization of Business Education Curricular in Nigerian Universities and Avoiding Functional Dilemmas of Expectations and Realities - U, Amahi Fidelis (Journal of Education and Vocational Research, 2014)
The paper focuses on enhancing quality through the harmonization of business education curricular across the globe and Nigerian universities in particular. 35 graduate students from three tertiary institutions were randomly selected and 15 lecturers in business education were the sample subjects. The survey method was used to determine the effects of lack of uniformity in business education curriculum at graduate level the mean and standard deviation were used to analyze the items. The t-test statistics method was also used. It was found out that there was lack of uniformity in the curricula of business education at graduate level among other things. The paper recommends that supervisory authorities should harmonize the curricula of business education to ensure uniformity in tertiary institutions particularly at graduate level and to enhance and ensure quality of the programme. It also recommends that 80% of the course content in the core option areas be incorporated into the curriculum to enhance performance and learning outcome and avoid functional dilemma of expectation and realities.